Five Single-Nucleotide Polymorphisms in the PITX2 Gene as Risk Factors for Atrial Fibrillation - Putra, Rendra Mahardhika; Dharmadjati, Budi Bakti; Pikir, Budi Susetyo; , Irma Maghfirah; Isaridha, Ilma Alfia; Arnindita, Jannatin Nisa (Folia Medica Indonesiana, 2023)
Highlights: • A genetic variable has been identified as an atrial fibrillation risk factor. • Rs2200733 is a type of SNP that increases atrial fibrillation risk, whereas rs3853445, rs6838973, and rs17570669 have the reverse effect. Abstract: Atrial fibrillation (AF) is a highly prevalent arrhythmia. The involvement of molecular mechanisms in increased AF risk remains uncertain. However, the paired-like homeodomain transcription factor 2 or pituitary homeobox 2 (PITX2) gene has been linked to AF development. A comprehensive search was carried out to identify all eligible case-control studies in order to assess the association between five single-nucleotide polymorphisms (SNPs) in the PITX2 gene and the risk of AF. This meta-analysis employed the Review Manager (RevMan) software version 5.3 (Cochrane). There were 13 clinical studies, with a total of 11,961 subjects, that met the inclusion criteria. These subjects consisted of 4,440 patients with AF and 7,521 controls. The meta-analysis of five SNP types in the PITX2 gene was done using crude odds ratios (ORs). This revealed that rs2200733 increased the risk of AF (OR=1.80; 95% CI=1.53-2.11; p=0.0005; I2=80%). On the other hand, the other three SNPs decreased the risk of AF, namely, rs385344 (OR=0.75; 95% CI=0.59-0.95; p=0.002; I2=85%), rs6838973 (OR=0.64; 95% CI=0.51-0.81; p=0.0001; I2=73%), and rs17570669 (OR=0.80; 95% CI=0.65-0.98; p=0.03; I2=70%). However, there was no significant association between rs10033464 and AF (OR=1.21; 95% CI=0.97-1.50; p=0.13; I2=83%). In conclusion, depending on the type, SNPs in the PITX2 gene correlate with AF risk factors, either by alleviating or reducing the risk.